Discerning states' revisionist and status-quo orientations: Comparing China and the US. (June 2019) - Chan, Steve; Hu, Weixing; He, Kai
International Relations literature often refers to states' motivations as revisionist or status-quo oriented. Such attributions are especially prevalent in discourse on the power-transition theory, suggesting that the danger of war rises when a revisionist China catches up to a status-quo US. Such attributions, however, are rarely supported by systematic evidence providing a direct comparison of Chinese and US conduct. We undertake an analysis of how these countries have behaved differently over time according to their policy pronouncements, their participation in international institutions and agreements, and their voting in the United Nations. Our analysis challenges the conventional wisdom that a rising power tends to be revisionist whereas an incumbent hegemon is invariably committed to the defense of the international order.